Strategic management practises in construction industry: a Malaysian experience - Bakar, Abu Hassan Abu; Said, Ilias; Razak, Arman Abdul; Yusof, Mohamad Nizam (2008)

(untitled)
This paper investigates the practices of strategic management by local construction companies in Malaysia. Strategic management is a concept that concerns with making decisions and taking corrective actions to achieve long term targets and goals of an organization. Although strategic management has until recently been a low-profile activity within many construction firms, it is now becoming more widely used by many large organizations that are allocating substantial resources to the task. Generally, strategic management practices can improve efficiency in various organizations - large and small, for profit and non-profit, private and public. Questionnaires were distributed to 300 large construction companies listed under G7 groups classified by the Construction Industry Development Board (CIDB). The response rate of the survey is 26% or 78 construction companies having replied. The findings of the research showed that most of the firms practicing strategic management have a clear objective, a winning strategy to achieve the objective and a sound mission statement to guide the organization towards success.